Rapid “Breath-Print” of Liver Cirrhosis by Proton Transfer Reaction Time-of-Flight Mass Spectrometry. A Pilot Study - Morisco, Filomena; Aprea, Eugenio; Lembo, Vincenzo; Fogliano, Vincenzo; Vitaglione, Paola; Mazzone, Giovanna; Cappellin, Luca; Gasperi, Flavia; Masone, Stefania; De Palma, Giovanni Domenico; Marmo, Riccardo; Caporaso, Nicola; et al. (PloS one, 2013)
The aim of the present work was to test the potential of Proton Transfer Reaction Time-of-Flight Mass Spectrometry (PTR-ToF-MS) in the diagnosis of liver cirrhosis and the assessment of disease severity by direct analysis of exhaled breath. Twenty-six volunteers have been enrolled in this study: 12 patients (M/F 8/4, mean age 70.5 years, min-max 42-80 years) with liver cirrhosis of different etiologies and at different severity of disease and 14 healthy subjects (M/F 5/9, mean age 52.3 years, min-max 35-77 years). Real time breath analysis was performed on fasting subjects using a buffered end-tidal on-line sampler directly coupled to a PTR-ToF-MS. Twelve volatile organic compounds (VOCs) resulted significantly differently in cirrhotic patients (CP) compared to healthy controls (CTRL): four ketones (2-butanone, 2- or 3- pentanone, C8-ketone, C9-ketone), two terpenes (monoterpene, monoterpene related), four sulphur or nitrogen compounds (sulfoxide-compound, S-compound, NS-compound, N-compound) and two alcohols (heptadienol, methanol). Seven VOCs (2-butanone, C8-ketone, a monoterpene, 2,4-heptadienol and three compounds containing N, S or NS) resulted significantly differently in compensate cirrhotic patients (Child-Pugh A; CP-A) and decompensated cirrhotic subjects (Child-Pugh B+C; CP-B+C). ROC (Receiver Operating Characteristic) analysis was performed considering three contrast groups: CP vs CTRL, CP-A vs CTRL and CP-A vs CP-B+C. In these comparisons monoterpene and N-compound showed the best diagnostic performance. Breath analysis by PTR-ToF-MS was able to distinguish cirrhotic patients from healthy subjects and to discriminate those with well compensated liver disease from those at more advanced severity stage. A breath-print of liver cirrhosis was assessed for the first time.